Self-government and self-defence in South Africa: the inter-relations between British and Cape politics, 1846-1854 - Kirk, T (1972)
Any person studying the history of the Cape Colony in the mid- Victorian years must soon grow aware of the contrast between what the imperial authorities said they intended to do and what they actually did. This is particularly obvious in the treatment of the frontier tribes, who lost their lands (and sometimes their lives) in the name of a policy described by one governor as based on 'morality and religion'. But it is also evident in many other spheres of government, and insistently raises the question of that British intentions really were and how far Ministers managed to achieve them. The evidence available is too vast and amorphous for a gene- ral survey to be attempted. In order to investigate the problem it is necessary to limit its scope. The period from 1846 to 1854 has been chosen because it embraced two frontier wars and a series of major administrative changes, involving prolonged consultation between Government House and Downing Street, and raising matters which affected the vital interests of the colonial population itself. It is also ground covered by other historians, but they have frequently differed as to the aims of the imperial government and the colonial reaction to them. One reason for their differences is plain: they have failed to take a comprehensive view of the sub- ject, such as the imperial government itself might have taken. Frontier policy is described as if it bore no relation to constitutional changes in Cape Town; local politics are discussed as if the British connection had little relevance. Britain's treatment of the Afrikaners led one of their leaders to style the nineteenth century a 'Century of Wrong.‘ But those sympa- thetic to the British approach have seen in it an attempt to infuse the spirit of British tolerance and justice into Cane society. They explain its contradictions by depicting an imperial power those 'high natives and worthy ends were frustrated by the inadequate resources which could be spared for the resolution of Cape problems. The material on which this conclusion rests is predominantly that found in official archives in Cape Town and London. A glance at the bibliographies of works by de Kiewiet, Galbraith, Morrell and Macmillan reveals no systematic attempt to study newspapers or other sources to check the accuracy or discover the undertones of official reporting from the Colony. Furthermore, large collections of private correspondence belonging to prominent politicians have recently been made public in Britain. Although often edited of financial or other sensitive items they still raise similar doubts about the comprehend- siveness of Colonial Office despatches. A new assessment of these sources is therefore required. In 1867 Bagehot differentiated between the 'distinguished' and the 'efficient' parts of the British constitution. The former he described as designed to 'excite and preserve the reverence of the population'; the latter as 'those by which it, in fact, works and rules'. This thesis attempts to show that Colonial Office pronouncements on the Cape likewise fall into two categories. Some were intended (again borrowing Bagehot's words) to 'win the loyalty and confidence of mankind'; others to 'employ that homage in the work of governmental. From this it follows that the statements in despatches are not invariably to be trusted, and that some are of greater significance in the interaction of Cape and British politics than others. The private correspondence helps us to differentiate. It also shows the Colonial Office less as a place where policy was made and more as one where decisions taken by Mini- sters were translated into a form understandable to governors and acceptable to the British public. Continued in thesis ...